EVALUASI AWARENESS POP-UP WEBSITE BERDASARKAN DESAIN, KONTEN DAN NOTIFIKASI - Abdillah, Rahmad; Mai Candra, Reski (Riau Journal Of Computer Science, 2020)
Pop-Up is one of the tools that can increase an organization's revenue because one of its functions is to direct. However, many are abusing this pop-up function. Many pop-ups point users to gambling, data theft, and so on. Therefore users who do not care about this threat will be targeted. This study evaluates pop-up models that appear in terms of design, content, and notification aspects. A total of 163 respondents who had an Information Technology (IT) background were evaluated. The evaluation has passed the tests of normality, reliability, and homogeneity. Respondents feel disturbed by the presence of pop-ups, especially how to close the pop-ups that appear. At the end of the sub-discussion, there are implications of this study